2012
DOI: 10.1007/s00125-012-2582-5
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin reduces plaque macrophage content and stabilises arteriosclerotic lesions in Apoe −/− mice

Abstract: Aims/hypothesis Inhibitors of dipeptidyl peptidase-IV (DPP-IV), such as sitagliptin, increase glucagon-like peptide-1 (GLP-1) concentrations and are current treatment options for patients with type 2 diabetes mellitus. As patients with diabetes exhibit a high risk of developing severe atherosclerosis, we investigated the effect of sitagliptin on atherogenesis in Apoe −/− mice. Methods Apoe−/− mice were fed a high-fat diet and treated with either sitagliptin or placebo for 12 weeks. Plaque size and plaque compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 37 publications
5
57
0
3
Order By: Relevance
“…8 The capacity of incretin-modulating agents to influence plaque stability is not unprecedented with recent observations of increased plaque stability in the absence of a reduction in atherosclerotic disease burden being identified in DPP-4 inhibitor-treated ApoE −/− mice. 27 Interestingly, this study utilised a dietary protocol similar to protocol 2 used in our studies and suggests that plaque stabilisation can be initiated in early stage disease and continues with the establishment of high-burden atherosclerotic disease even in the absence of obvious treatment-mediated reduction in disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…8 The capacity of incretin-modulating agents to influence plaque stability is not unprecedented with recent observations of increased plaque stability in the absence of a reduction in atherosclerotic disease burden being identified in DPP-4 inhibitor-treated ApoE −/− mice. 27 Interestingly, this study utilised a dietary protocol similar to protocol 2 used in our studies and suggests that plaque stabilisation can be initiated in early stage disease and continues with the establishment of high-burden atherosclerotic disease even in the absence of obvious treatment-mediated reduction in disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Alogliptin treatment, in ApoE 2 /2 diabetic mice, induced a significant reduction of atherosclerotic lesions and a concomitant reduction of IL-6 and IL-1b (69). Vittone et al (70) showed that in ApoE 2/2 mice, sitagliptin reduced plaque inflammation and increased plaque stability, potentially by GLP-1-mediated inhibition of chemokine-induced monocyte migration and macrophage matrix metalloproteinase 9 release. Interestingly, it was shown that linagliptin administered in a rat model of sepsis ameliorated lipopolysaccharideinduced endothelial dysfunction in addition to reduced aortic infiltration with inflammatory cells (71).…”
Section: Literature Search Strategymentioning
confidence: 99%
“…Thus, this study was designed to identify differences in SIRT6 expression, as well as in inflammatory infiltration, between carotid plaques of asymptomatic diabetic and nondiabetic patients. Experimental studies suggest that in obese mice, GLP-1-based therapies may reduce inflammation (11)(12)(13) and enhance the protein expression of SIRT1 (14). Moreover, human studies showed that sitagliptin (15) and exenatide (16), even at a single dose, exert a potent anti-inflammatory effect, and that many of these effects were persistent over a period of 12 weeks, thus suggesting that the anti-inflammatory effects of GLP-1-based therapies could help to reduce atherogenesis.…”
mentioning
confidence: 99%